The Canal of many colours : a whimsical trip through the Panama Canal - Weil, Carlos (Weil Art Panama CityPA, 2009)
Offers a game involving imagination, dicipherment and amusement around history and art. Includes the work of seven artists, using different techniques applied against the background of the stock and bond certficates issued by the French Compagnie Universelle du Canal Interocéanique de Panama.